The Effectiveness of Acceptance and Commitment Therapy (ACT) for Reducing Depression in Post-Stroke Patients - Sari, Nurmalita; Utami, Margaretha Sih Setija; Rahayu, Esthy (Philanthropy: Journal of Psychology, 2022)
Abstract.  Stroke will experience setbacks such as difficulty in thinking, speaking and moving. This condition creates a feeling of helplessness with his life, so that post-stroke patients are prone to depression. The purpose of this study was to determine the effect of giving Acceptance and Commitment Therapy (ACT) in reducing depression in post-stroke patients. This study involved 6 post-stroke participants with major depression. The research method used was quantitative- true eksperiment. Based on the results of the Mann-Whitney posttest, there was a significant difference in scores between the groups that were given Acceptance and Commitment Therapy (ACT) and those who were not given Acceptance and Commitment Therapy (ACT) (0.023; p